Balancing international public goods and accountability: Exploring the impact of IFPRI’s policy research on science, technology, and innovation - Lynam, John K. (International Food Policy Research Institute, 2016)
The International Food Policy Research Institute (IFPRI) has undertaken research programs on agricultural STI policy since 1995. This study assesses the impact of this body of research outputs and support services in terms of three complementary analyses: (1) an evaluation of the potential impact of the complete body of research using implicit or explicit impact pathways, (2) two case studies that assess the actual impact of particular research outputs, and (3) a more traditional bibliometric analysis. Movement along the impact pathway, in turn, requires different types of research products—evolving from problem framing to methodology development, then to case studies, and finally to context-specific policy recommendations—all within the logical stages of the impact pathway. How far IFPRI operates along this impact pathway produces a basic tension between the CGIAR’s mandate to produce international public goods (IPGs) and the increasing focus on accountability through impact in the use of international public funds.